Cellulosic-based microneedles for sensing heavy metals in fish samples - Houman Kholafazad; Mahdiyeh Pazhuhi; Mohammad Hasanzadeh; Nicolas H. Voelcker; Nasrin Shadju; Azadeh Nilghaz (Carbohydrate Polymer Technologies and Applications)
Microneedles (MNs) have emerged as a cutting-edge sensing approach due to their enhanced surface area, improved sample penetration, localized detection, and potential for enhanced sensitivity. However, some MN manufacturing methods involve complex procedures, costly equipment, and non-biocompatible materials. Additionally, challenges in integrating MNs into existing technologies hinders their application in rapid and low-cost sensor technology. This study reports the development of innovative MNs fabricated using readily available cellulosic-based paper fibers, in which fibers from Whatman paper mixed with 1 % polyvinyl alcohol (PVA) were shaped using a polydimethylsiloxane (PDMS) mold. The MNs operate based on both physical penetration force and fluidic absorption via capillary action in the porous cellulosic matrix. The MNs exhibit low reagent and sample volume requirements along with flexibility and ease of penetration into samples, and filtration capabilities that allow efficient detection with minimal interference. The structure of MNs was investigated by field emission scanning electron microscopy (FE-SEM), revealing a conical shape with an average height of ∼750 µm and a diameter of ∼500 µm. The performance of the MN sensors was validated by colorimetric detection of heavy metals in fish, demonstrating linear ranges of 0.6 to 8 mg/L, 0.2 to 4 mg/L, and 0.3 to 6 mg/L for copper Cu(II), chromium Cr(VI), and nickel Ni(II), respectively. The colorimetric detection, combined with smartphone-based digital image analysis, exhibited lower limit of quantification (LLOQ) of 0.6, 0.2, and 0.3 mg/L for Cu(II), Cr(VI), and Ni(II), respectively, with no significant interference in the presence of potential interfering ions.